The Potential of Indonesian Textbooks in Stimulating Students' Learning Activities - Huda, Miftakhul; Anjas Rusdiyanto Soleh; Nadia Zakiyyah; Safira Inayatul Maula; Siwi Nur Arifah; Retno Astri Ardaninggar (Journal of Education Reseach and Evaluation, 2024)
Not all Indonesian language textbooks are able to stimulate student learning activities optimally. Many textbooks have yet to be designed with students' cognitive and motivational needs in mind. This research aims to identify the potential of Indonesian language textbooks in stimulating student learning activities. This type of research is qualitative research with a case study method. The research sample was chosen purposively, namely one Indonesian language textbook used in one of the secondary schools. Data was collected through observation, interviews, literature study, and document analysis. The instruments used were interview and observation guidelines. The data analysis method used is the spiral model data analysis technique. The research results show that textbooks can be an effective stimulus in stimulating student learning activities. Some ways textbooks can stimulate student activity include presenting interesting material, encouraging reflection and discussion, and providing project-based assignments. Overall, Indonesian language textbooks have great potential to increase student learning activities. The application of this research is that the use of appropriate textbooks can motivate students, broaden their participation, and improve learning achievement.